Metataxonomic Analysis of Grape Microbiota During Wine Fermentation Reveals the Distinction of Cyprus Regional terroirs - Kamilari, Eleni; Mina, Minas; Karallis, Christos; Tsaltas, Dimitrios (Frontiers in Microbiology, 2021)
Wine production in Cyprus has strong cultural ties with the island's tradition, influencing local and foreign consumers' preferences and contributing significantly to Cyprus' economy. A key contributor to wine quality and sensorial characteristics development, is the microbiota that colonizes grapes and perform the process of alcoholic fermentation. Still, the microbial patterns of wines produced in different geographic regions (terroir) in Cyprus remain unknown. The present study investigated the microbial diversity of five terroir in Cyprus, two from PGI Lemesos region [Kyperounta (PDO Pitsilia) and Koilani (PDO Krasochoria)], and three from PGI Pafos region [Kathikas (PDO Laona Akamas), Panayia and Statos (PDO Panayia)], producing wines from two grape varieties, Xynisteri and Maratheftiko, using High-Throughput Sequencing. Through a longitudinal analysis we examined the evolution of the microbial diversity during spontaneous alcoholic fermentation. Both varieties were characterized by a progressive reduction in their fungal alpha diversity (Shannon index) throughout the process of fermentation. Additionally, the study revealed a distinct separation among different terroirs, in total fungal community composition (beta-diversity) for the variety Xynisteri, and among Kyperounta from the other terroirs for the variety Maratheftiko, from grape juice, until post-fermentation must. Also, a significant distinction was demonstrated in total bacterial diversity between the PGI Lemesos region and of the PGI Pafos region terroirs, for grape juice of the variety Xynisteri. Pre-fermentation, the fungal diversity both for Xynisteri and Maratheftiko, was dominated by genera such as Hanseniaspora, Aureobasidium, Erysiphe, Aspergillus, Stemphylium, Penicillium, Alternaria, Cladosporium and Mycosphaerella. During and post-fermentation, the species Hanseniaspora nectarophila, Saccharomyces cerevisiae, Hanseniaspora guilliermondii and Aureobasidium pullulans, became the predominant in most must samples. Regarding the bacterial diversity, Lactobacillus and Streptococcus were the predominant genera for both grape varieties in all stages of fermentation. During fermentation, an increase was observed in the relative abundance of some bacteria, such as Acetobacter, Gluconobacter and Oenococcus oeni. Finally, the study revealed microbial biomarkers with statistically significant increase relative representation, associated with each geographic region, as well as each grape variety, during the different stages of fermentation. The present study's findings provide an additional linkage between the microbial communities’ composition and activity with the wine terroir.